PENGARUH PERSEPSI HARGA, KUALITAS LAYANAN DAN LOKASI TERHADAP KEPUTUSAN PEMBELIAN PADA RUMAH MAKAN ALAM KINCAI DESA KARYA BAKTI KOTA SUNGAI PENUH - Zefri Efdison (LPPM - STIE SAKTI ALAM KERINCI, 2018)
This study aimsto determine The extent of the influence of price perceptions on purchasing decisions at kincai nature restaurants then The extent of the influence of service quality on the location of the kincai nature restaurant then the extent to which the influence of price perceptions on purchasing decisions in natural restaurant kincai both directly and indirectly then The extent to which the influence of service quality on purchasing decisions in natural restaurant kincai both directly and indirectly then The extent of the influence of location on purchasing decisions at kincai nature restaurant.The population in this study were all customers and buyers totaling 90 people, by using accidental sampling the data analysis tool used is multiple linear regresions, average score, and hypothesis testing.Based on the research result show that : Price perception has a positive and significant effect on purchasing decisions at Kincai Nature Restaurant, service quality has a positive and significant effect on purchasing decisions, location does not have an effect and is not significant to the purchasing decisions. Simultaneously the perception of price and service quality has a positive and significant effect on purchasing decisions, while the location is negative and insignificant towards purchasing decisions at kincai natural restaurant.